Experimental processes through artistic communication in the theurapeutic approach of women affected by trauma - Navajas Seco, Rosaura (Arteterapia. Papeles de arteterapia y educación artística para la inclusión social, 2018)
The social responses to the situation of those women who have suffered from abuse are not enough to meet their demands, as far as what we understand as a real inclusion in our society is concerned. Helping them recover their own lives (both psychologically and emotionally) requires intervention programmes which shall include inclusive policies in all fields. It is important for the links of the aid chain to remain unbroken in an already complicated system that starts when a woman reports the incident to the police and finishes when she eventually feels socially included as a citizen. The programmes that aim to improve the emotional and psychophysical status of abused women do remarkably help them to normalise their daily situation and their social relation. The implementation of a programme that includes different expressive types of communication* such as music, painting and body language, is crucial in the empowerment of these people. Our line of action, far from just working on the cognitive area in the treatment of women, proposes an implementation of programmes that include the cognitive, affective and experiential areas at their core, and it does so through different activities that have their focal point on different artistic communication systems. We shall analyse the body of a woman who is conscious, who feels and takes action to assert her own identity and her relationship with the world.